Women, gender, remittances and development in the Global South - Naerssen, A. L. van (Gender in a global/local world, 2015)
The book questions such gender myths. Its great value for practitioners and academics lies in its sensitivity to power relations as well as to local contexts. It is fascinating how gendered decision-making and identities are changing through remittances in even contradictory ways. Hence, there is no generic policy recipe.